PENINGKATAN PRODUKTIVITAS EMPING MLINJO MELALUI PENGEMBANGAN MESIN SANGRAI, WEB, DAN MANAJEMEN USAHA - Aan Ardian, Aman, Lia Yuliana (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
One of the flag ship products of Bantul area is a traditional food product that is made from chips mlinjo based mlinjo. For rural areas, potential areas of Bantul strongly supports the development of traditional food craft industry mlinjo chips. Mlinjo plants are very easy to get in Bantul. Melinjo kind of chips are made from fruit that has been melinjo old. Making chips is not difficult and can be done using simple tools. Mlinjo is one of the processing of agricultural commodity prices are high. These commodities can be exported to neighboring countries. But the fact is lack of capital held, the lack of touch technology in the production process, especially in the roaster mlinjo quickly, applied management system is very simple, so profits and losses can not be detected properly, yet have the ability to use information technology can be used as a marketing medium. To achieve these objectives, the methods used in this activity is the creation of training mlinjo roaster machine that can be adjusted as needed to improve the quality and quantity. Web design training to support the marketing of products crackers mlinjo, business management training. IbM Small Industries Group activities Craftsmen Emping mlinjo in Beji, displays Bantul Yogyakarta for 3 days on 3, 4, and 5 November 2013 at 07:30 to 16:30 pm. In general, all participants followed the events with high motivation and earnest. It is evident in their attendance on a regular basis for three days and follow each session with care and enthusiasm. The questions they launched during the opening session. Things are less clear they as to obtain understanding. The first day of training activities, participant follow carefully. They feel they have received during this new knowledge they do not know, the participants became more familiar. Keywords: small industries group, emping mlinjo